Application of Bromoxynil+MCPA+Metribuzin at Varied Doses for Broad-Spectrum Weed Control in Forage Maize (Zea mays L.): Weed Control in Forage Maize (Biological Sciences - PJSIR, 2019)
Weed control is one of the crucial factors to achieve higher yield of good quality forage maize. A field trial was conducted during summer 2013 to investigate the effect of bromoxynil+MCPA+metribuzin (Valent 470 EW pre mixed formulation) application at varied doses to control weeds in forage maize (Zea mays L.) at Agronomy Research Area, University of Agriculture, Faisalabad, Pakistan. Application of  bromoxynil+MCPA+metribuzin @ 470, 528.75 and 587.50 g a.i/ha was made after emergence of weedsand crop. A check with no application and hand hoeing was included for comparison. The experiment was conducted with four replications under randomized complete block design. The data regarding the weed parameters, yield and yield components of maize were recorded. The results revealed that among the herbicide treatments minimum weed density (three weeks after sowing 35.75 m2 and at harvest 12.25/m2) and dry biomass (20.80 g/m2) was observed with the application of bromoxynil+MCPA+metribuzin @ 587.50 g a.i./ha. Same herbicidal treatment caused significant increase in plant height (248.75 cm), stem diameter (1.45 cm), fresh weight (467.25g) and forage yield (31.47%) of maize. Therefore, use ofbromoxynil+MCPA+metribuzin @ 587.50 g a.i./ha is the best option to manage broad leaved as well as grassy weeds in forage maize to get higher yield of forage .